2v+29=-9(v+9)

Simple and best practice solution for 2v+29=-9(v+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2v+29=-9(v+9) equation:


Simplifying
2v + 29 = -9(v + 9)

Reorder the terms:
29 + 2v = -9(v + 9)

Reorder the terms:
29 + 2v = -9(9 + v)
29 + 2v = (9 * -9 + v * -9)
29 + 2v = (-81 + -9v)

Solving
29 + 2v = -81 + -9v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '9v' to each side of the equation.
29 + 2v + 9v = -81 + -9v + 9v

Combine like terms: 2v + 9v = 11v
29 + 11v = -81 + -9v + 9v

Combine like terms: -9v + 9v = 0
29 + 11v = -81 + 0
29 + 11v = -81

Add '-29' to each side of the equation.
29 + -29 + 11v = -81 + -29

Combine like terms: 29 + -29 = 0
0 + 11v = -81 + -29
11v = -81 + -29

Combine like terms: -81 + -29 = -110
11v = -110

Divide each side by '11'.
v = -10

Simplifying
v = -10

See similar equations:

| 49=r+32 | | 6z+15=6(z+4)-14 | | -5x-1.5+8=2.5-1x | | 2v+29=9(v+9) | | x^2-25x+150= | | 6x+0.3= | | 3x-2.5+4=4.5+x | | -42=-7 | | 118x=1/3 | | 46+7.3g=46.0365 | | 5(4x-7)=-21(5-x) | | 1/3x=118 | | (8h-1)-(h+3)h=-3 | | y=(2x-1)/(4) | | 5/6(6t-6)-3 | | 2(96+l)+2(60+w)= | | -7u+5(u-2)=-14 | | 118x=2/3 | | 3b+14=11 | | pq=y | | 6x+8x-5=23 | | Lnx-7=-3.2 | | 2x+36y=-1 | | 1=2n-n | | 12x+1=3(4x+1) | | 6(d+9)=90 | | y=2x-1/4 | | k/3-3=4 | | Q/4-1=5 | | 2x-4+0.2+0.3=7 | | X+6.2=9.1 | | 11f-(-2f+2)f=.5 |

Equations solver categories